The potential of subtitling as a UDL tool. Future Secondary Education Teachers’ perceptions in Spain: Percepción de los futuros profesores de lenguas de Educación Secundaria en España - Hunt-Gómez, Coral Ivy (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Subtitling has a great didactic potential that facilitates universal learning design. Through the analysis of perceptions with quantitative and qualitative data, this work aims to know both the previous ideas about the pedagogical uses of subtitling and the perception of future language teachers of secondary education of its potential as a didactic tool or resource that favours integration. The results show that language teachers of Secondary Education are familiar with subtitling as consumers, but they need pedagogical training to include it in their teaching practice and thus, make teaching more inclusive.